The Barrier Zones in the Ocean - Emelyanov, Emelyan M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Geochemical barrier zones play an important role in determining various physical systems and characteristics of the oceans, e.g. hydrodynamics, salinity, temperature and light. In this book, each of the 40 barrier zones covered are illustrated and defined by physical-chemical parameters. Among the topics discussed are the processes of inflow, transformation and precipitation of the sedimentary layer of the open oceans and more restricted areas such as the Baltic, Black and Mediterranean Seas. This well-illustrated book may serve as the basis for courses such as "Marine Geochemistry" or "Ocean Usage" and can be useful to researchers in the fields of geology, geography, marine chemistry, geoecology and hydrochemistry.
Brief Characteristics and Classification of Barriers and Barriers Zones in the Ocean -- Mechanical (Hydrodynamic) Barriers -- Physicochemical Barriers -- Salinity Barriers -- Temperature, Density and Dynamic Barriers -- Geochemical Barriers That Exist Independently of Their Position in Space (Autonomic Barriers) -- Geochemical Barrier Zones -- Geochemical Landscapes -- Barriers as transformation areas of sedimentary material -- River-Sea -- Coast-Sea -- Hydrofronts -- Front of Coastal Upwelling -- Ice-Water Boundary -- Hydrothermal Fluid-Seawater Barrier Zone -- Ocean-Atmosphere -- Photic Layer -- The Thermocline and Pycnocline as GBZs -- Oxygen Minimum Layer -- Redox (Eh) Barrier in Seawater -- Salinity Barrier -- Calcium Carbonate Compensation Depth (CCD) -- The Water-Bottom Interface -- Redox (Eh) Barrier in Sediments -- The Upper Active Sediment Layer -- Lithogeochemical Areas, Regions and Provinces -- Lithogeochemical Barriers as Leading Factors in Ore Formation -- General -- Mechanical Barriers and Placer Formation -- River-Sea GBZs and Formation of Oil Hydrocarbons -- River-Sea GBZs and Formation of Pseudo-oolitic and Oolitic Hydrogoethite-Chamosite Ferruginous Ores and Glauconite -- Front of Coastal Upwelling and Accumulation of Phosphorites -- Hydrofronts and Ore Formation in Pelagic Areas of the Ocean -- The Halocline (Pycnocline) and Accumulation of Shallow-water Ferromanganese Crusts and Nodules -- The Oxygen Minimum Layer and Development of Cobalt-Manganese Crusts -- Geochemical Barrier Zones and Processes of Accumulation of Carbonate-Oxic Manganese Ores -- Ore Formation at the Redox (Eh) Barrier in Sediments -- Geochemical Barrier Zones and Formation of Siderite -- Hydrothermal Process and Ore Formation -- Calcium Carbonate Compensation Depth and Formation of FMNs -- Geochemical Barrier Zones and Formation of Sapropel -- Predicting and Prospecting for Ores of Marine Genesis -- Some Geological Aspects of Variations in Marine -- Second-Order Boundaries -- First-Order Boundaries -- Internal Boundaries.
Keywords: Oceanography; Geochemistry; Oceanography; Geochemistry